ժամանակակից հայերենի բաղադրական հիմքերի տարբերակային ձևերը - Արամ Խաչատրյան (Տաթև գիտակրթական համալիր, ՀՀ ԳԱԱ Հ. Աճառյանի անվան լեզվի ինստիտուտ)
Данный доклад посвящен вариативным формам составных основ современного армянского языка. На основе материалов грабара (древнеармянский язык) ашхарабара (современный армянский язык) были исследованы эти особенности основ, показаны изменения в результате исторического развития и их тенденции.On the bases of the factual material of Old Armenian and Modem Armenian the paculiarities of the bases are investigated, the changes and their tendencies realized during the historical development of the language are shown. Three versions of constitive bases are distinguished in the article: the typological, the phonetic and the historic, with their variants.
Keywords: Լեզվաբանություն; Բառարանագրություն